Predictive Analytics for Clothing Store using Artificial Neural Network - Mohd Jafri, Nur Farah Jazlin (IRC, 2019)
Predictive analysis is a sophisticated data engineering part that usually predicts some data-based event or probability. Predictive analytics utilizes data-mining methods to predict and create suggestions depending on these projections about potential occurrences. The method includes analysing historical information and predicting potential events or events depending on that assessment. Using predictive analytics modelling methods, a design can be developed to estimate. Depending on the data they use, the form of these predictive models varies. The two primary goals of predictive analytics are classification & regression. Predictive Analytics consists of different statistical & analytical methods that are used to create designs that forecast potential event, occurrences or probabilities. Not only can predictive analytics cope with ongoing modifications, but also with discontinuous modifications. Classification, prediction, and to some extent, affinity analysis constitutes the analytical methods employed in predictive analytics.